2019
DOI: 10.1038/s41598-019-46795-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of chlorine dioxide to sterilize medium for tissue culture of potato

Abstract: In vitro cultured seedlings or microtubers are the major starting materials for the production of potato. Currently, seedlings are cultured in media sterilized by autoclaving, which, however, consumes more electricity and takes longer for sterilization, and also requires high temperature-tolerant vessel materials. In order to identify alternative methods of sterilizing culture conditions, the disinfection effects of chlorine dioxide (CD) at 88.0, 29.3, 17.6, 12.6 and 8.8 μM were evaluated in potato … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…found that hydrogen dioxide had a better sterilization effect on potato micropropagation and caused no damage to seedling growth and tuber induction [27]. These results indicate that different bacteriostatic agents are suitable for a range of explant sterilization methods.…”
Section: Discussionmentioning
confidence: 81%
“…found that hydrogen dioxide had a better sterilization effect on potato micropropagation and caused no damage to seedling growth and tuber induction [27]. These results indicate that different bacteriostatic agents are suitable for a range of explant sterilization methods.…”
Section: Discussionmentioning
confidence: 81%
“…Chlorine dioxide was also used to sterilize the medium for tissue culture of potato ( Solanum tuberosum L .) [ 56 ]. NaOCl can alleviate significantly the inhibitive effect of salt stress during the germination phase.…”
Section: Resultsmentioning
confidence: 99%
“…Using chemicals instead of autoclaving has drawn attention because it is an easily applicable method to decontaminate culture medium. Several chemicals, including antibiotics [13], fungicides [14], plant preservative mixtures [15], chlorine dioxide [16,17], diethyl pyrocarbonate [18], peracetic acid [19], sodium hypochlorite [20][21][22], hydrogen peroxide [23],…”
Section: Introductionmentioning
confidence: 99%